Perspektif Izin Ninik Mamak sebagai Prasyarat Pernikahan Perspektif Hukum Islam - intan tri handayani intan (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article discusses the ninik mamak permit mechanism as a prerequisite for marriage in Bungo Dani District, Bungo Jambi Regency. The method used is qualitative with an interpretative/hermeneutic approach by collecting data using observation, interviews, and documentation. The findings in this study include; first, the ninik mamak permit mechanism as a prerequisite for marriage, namely the preparation period, fiancÃ©, â€œmengantar â€œsirih tanyo pinang tanyo,â€ â€œmengembang tando,â€ and